Monetary policy spillovers, capital controls and exchange rate flexibility, and the financial channel of exchange rates - Georgios Georgiadis; Feng Zhu (European Central Bank (ECB), 2019)
We assess the empirical validity of the trilemma (or impossible trinity) in the 2000s for a large sample of advanced and emerging economies. To do so, we estimate Taylor-rule type monetary policy reaction functions, relating the local policy rate to real-time forecasts of domestic fundamentals, global variables, as well as the base-country policy rate. In the regressions, we explore variations in the sensitivity of local to base-country policy rates across different degrees of exchange rate flexibility and capital controls. We find that the data are in general consistent with the predictions from the trilemma: Both exchange rate flexibility and capital controls reduce the sensitivity of local to base-country policy rates. However, we also find evidence that is consistent with the notion that the financial channel of exchange rates highlighted in recent work reduces the extent to which local policymakers decide to exploit the monetary autonomy in principle granted by flexible exchange rates in specific circumstances: The sensitivity of local to base-country policy rates for an economy with a flexible exchange rate is stronger when it exhibits negative foreign-currency exposures which stem from portfolio debt and bank liabilities on its external balance sheet and when base-country monetary policy is tightened. The intuition underlying this finding is that it may be optimal for local monetary policy to mimic the tightening of base-country monetary policy and thereby mute exchange rate variation because a depreciation of the local currency would raise the cost of servicing and rolling over foreign-currency debt and bank loans, possibly up to a point at which financial stability is put at risk.
Keywords: F42; E52; C50; 330; Trilemma; financial globalisation; monetary policy autonomy; spillovers